Comparative Study of Dual Therapy vs Triple Therapy in Severe COPD Management - Haider , Hafiz Muhammad Ali; Riaz , Muhammad Hamza; Shakeel, Zunaira; Shakeel, Izzah; Rehman, Muhammad Abdul ur; Pal, M Haadi Ashal (Indus Journal of Bioscience Research, 2025)
Introduction: Chronic obstructive pulmonary disease (COPD) is a leading cause of morbidity and mortality globally. The management of severe COPD typically involves pharmacological therapies aimed at symptom relief and disease progression slowing. Objective: To assess the effectiveness and safety of dual therapy compared to triple therapy in patients with severe COPD, focusing on exacerbation rates, lung function improvement, and quality of life over 12 months. Methodology: This prospective cohort study was conducted at Sheikh Zayed Teaching Hospital Rahim Yar Khan during 1st July 2024 to 31st December 2024, involving 230 patients with severe COPD, aged 40-80 years, who were recruited from outpatient clinics. These patients were randomly assigned to one of two groups: the dual therapy group (LABA + ICS) and the triple therapy group (LABA + ICS + LAMA). Results: The triple therapy group showed a significant reduction in exacerbation rates (40%) compared to the dual therapy group (25%). Lung function improved significantly in both groups, with a greater improvement observed in the triple therapy group (mean FEV1 increase of 200 mL compared to 150 mL in the dual therapy group). Quality of life, as measured by the CAT score, improved more significantly in the triple therapy group (mean reduction of 6 points) compared to the dual therapy group (mean reduction of 4 points). Conclusion: Triple therapy was found to be more effective in reducing exacerbation rates and improving lung function and quality of life compared to dual therapy in patients with severe COPD.